Circumscription and compromise : a developmental theory of occupational aspirations - Gottfredson, Linda S. [Verfasser] (My University, 1981)
„The article presents a developmental theory of occupational aspirations by providing definitions of key constructs, by reviewing evidence showing that all social groups share the same images of occupations, and by formulating a hypothetical cognitive map of occupations that summarizes those images and the dimensions of people's occupational preferences. Also described is the progressive and usually permanent circumscription of occupational preferences according to one's developing self-concepts. Four stages of development of self-concept and preferences are proposed: orientation to size and power (ages 3–5 years), orientation to sex roles (ages 6–8 years), orientation to social valuation (ages 9–23 years), and orientation to the internal, unique self (age 14 years). This development is considered to be highly conditioned by both cognitive development and one's social environment (e.g., social class). People's perceptions of their opportunities for implementing their choices and the priorities they use in reaching a compromise among conflicting goals are examined.“ (publisher; BIBB-Doku)
Keywords: L 5 Beratung & Orientierung; 370; 300; Berufswahl; Berufswunsch; Berufswahltheorie; Berufsorientierung; Selbstbild